2018
DOI: 10.1111/ecc.12934
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, cancer-related fatigue, and quality of life in patients with resected lung cancer

Abstract: We aim to investigate the relationship between self‐efficacy, cancer‐related fatigue, and quality of life in patients with resected lung cancer. A prospective cohort among 452 patients with resected NSCLC was conducted in 2014 to 2015. The self‐efficacy, cancer‐related fatigue, and quality of life assessments were investigated in the 3‐month follow‐up by General Self‐Efficacy Scale (GSES), Multidimensional Fatigue Symptom Inventory–Short Form (MFSI‐SF), and Short Form Health Survey (SF‐36), respectively. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Among the siblings however, self-efficacy was associated only with the HRQoL parameters general health and mental health. The findings are supported by previous research investigating quality of life and self-efficacy in adult cancer patients [ 41 , 42 ]. Social support showed to be of importance among both YA ALL survivors and the siblings regarding general health, vitality, mental health and depression.…”
Section: Discussionsupporting
confidence: 88%
“…Among the siblings however, self-efficacy was associated only with the HRQoL parameters general health and mental health. The findings are supported by previous research investigating quality of life and self-efficacy in adult cancer patients [ 41 , 42 ]. Social support showed to be of importance among both YA ALL survivors and the siblings regarding general health, vitality, mental health and depression.…”
Section: Discussionsupporting
confidence: 88%
“…The possible reasons might involve that (1) According to existing evidence, reminiscence therapy could improve the self-efficacy and problem-solving ability, which could make up for the deficiency caused by cancer-related functional impairments and further promote QoL in post-operational NSCLC patients. [20][21][22] (2) On the basis of previous findings in our present study, RTCP could promote mental health in NSCLC patients, and considering that depression and anxiety were risk factors for QoL, RTCP might improve QoL indirectly via positively affecting mental status of post-operational NSCLC patients. Interestingly, the results in our study demonstrated that there existed a numerical decreased longitudinal trend in rate and severity of anxiety and depression in RTCP group from M0 to M12, which also implied the effect of RTCP in post-operational NSCLC patients.…”
Section: Discussionmentioning
confidence: 61%
“…In current study, we observed that RTCP exhibited better effect on improving QoL compared with CCP in post‐operational NSCLC patients. The possible reasons might involve that (1) According to existing evidence, reminiscence therapy could improve the self‐efficacy and problem‐solving ability, which could make up for the deficiency caused by cancer‐related functional impairments and further promote QoL in post‐operational NSCLC patients 20‐22 . (2) On the basis of previous findings in our present study, RTCP could promote mental health in NSCLC patients, and considering that depression and anxiety were risk factors for QoL, RTCP might improve QoL indirectly via positively affecting mental status of post‐operational NSCLC patients.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, insomnia, dyspnea, and cough in patients with lung cancer receiving chemotherapy can also affect CRF (Long, Thanasilp, & Thato, 2016). This persistent symptom significantly reduces the quality of life (QOL) in patients with lung cancer (Chen, Liu, & You, 2018; Molassiotis, Lowe, Blackhall, & Lorigan, 2011). Although the underlying pathophysiology of this condition remains unclear, it could be attributed to the outcome of cancer itself and/or the side effects of chemotherapy and radiation therapy (Hofman, Ryan, Figueroa‐Moseley, Jean‐Pierre, & Morrow, 2007).…”
Section: Introductionmentioning
confidence: 99%